Formation of political censorship institution in Soviet Byelorussia (1917–1922) - Huzhalouski, Alexander A. (Journal of the Belarusian State University. History, 2018)
Оn the basis of archival sources, periodicals and contemporary research works, formation of political censoring system in the Soviet Byelorussia is presented in the article. The author gives an opportunity to a reader to examine the departmental period of censorship when political control was carried out simultaneously by the Belarusian Communist Party, Soviet administrative bodies, as well as the Red Army and political police. Combined they constituted censoring system which put under control all the intellectual production in Soviet Belarus – books and periodicals, theatrical plays and musical pieces.